Medium-vessel vasculitis following COVID-19 moderna (mRNA-1273) vaccination and the utility of PET-CT as a diagnostic tool: a case report - Martin H. Cherk; Luigi Zolio; Sadid Khan; Sharmayne Brady (EJNMMI Reports)
Abstract There have been several case reports of COVID-19 “BNT162b2” (Pfizer-BioNTech) and “mRNA-1273” (Moderna) vaccination associated small and medium vessel vasculitis described in the literature however none have had 18F-FDG Positron Emission Tomography scans (PET/CT) performed for diagnosis. We report the case of a 57-year-old Caucasian male patient from Australia where 18F-FDG PET/CT scanning facilitated early detection of a medium-vessel vasculitis following Moderna (mRNA-1273) COVID-19 vaccination. The diagnosis would otherwise have been difficult and allowed exclusion of alternative diagnoses and sparing of more invasive investigations such as muscle biopsy. Our case highlights the development of a medium vessel vasculitis following mRNA based COVID-19 vaccination and demonstrates the utility of 18F-FDG PET/CT as an excellent non-invasive test for the detection of this serious rare and often difficult to diagnose condition.